A Nuclease from Streptococcus mutans Facilitates Biofilm Dispersal and Escape from Killing by Neutrophil Extracellular Traps - Liu, Jia; Sun, Luping; Liu, Wei; Guo, Lihong; Liu, Zhaohui; Wei, Xi; Ling, Junqi (Frontiers in Cellular and Infection Microbiology, 2017)
Streptococcus mutans is the primary etiologic agent of dental caries and occasionally infective endocarditis, with the ability to form biofilms and disperse cells into distal sites to exacerbate and spread infection. In this study, we identified a nuclease (DeoC) as a S.mutans biofilm dispersal modulating factor through microarray analysis. In vitro assays revealed a dispersal defect of a deoC deletion mutant, and functional studies with purified protein were indicative of the biofilm dispersal activity of DeoC. Neutrophils are a key host response factor restraining bacterial spreading through the formation of neutrophil extracellular traps (NETs), which consist of a nuclear DNA backbone associated with antimicrobial peptides. Therefore, we hypothesized that the dispersed S. mutans might utilize DeoC to degrade NETs and escape killing by the immune system. It was found that S. mutans induced NET formation upon contact with neutrophils, while the presence of NETs in turn enhanced the deoC expression of S. mutans. Fluorescence microscopy inspection showed that deoC deletion resulted in a decreased NET degradation ability of S. mutans and enhanced susceptibility to neutrophil killing. Data obtained from this study assigned two important roles for DeoC in S. mutans: contributing to the spread of infection through mediating biofilm dispersal, and facilitating the escape of S. mutans from neutrophil killing through NET degradation.